2019
DOI: 10.3390/md17040238
|View full text |Cite
|
Sign up to set email alerts
|

Activation Studies of the γ-Carbonic Anhydrases from the Antarctic Marine Bacteria Pseudoalteromonas haloplanktis and Colwellia psychrerythraea with Amino Acids and Amines

Abstract: The γ-carbonic anhydrases (CAs, EC 4.2.1.1) present in the Antarctic marine bacteria Pseudoalteromonas haloplanktis and Colwellia psychrerythraea, herein referred to as PhaCA and CpsCA, respectively, were investigated for their activation with a panel of 24 amino acids and amines. Both bacteria are considered Antarctic models for the investigation of photosynthetic and metabolic pathways in organisms adapted to live in cold seawater. PhaCA was much more sensitive to activation by these compounds compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Activation studies were also performed recently against c-CAs, such as Zn-Cam and Co-Cam (from the Archaeon Methanosarcina thermpophila), BpscCA (from the pathogenic bacterium Burkhalderia pseudomallei), PhaCA (from the cyanobacterium Pseudoalteromonas haloplanktis), and CpsCA (from another cyanobacteriu, Colwellia psychrerythraea), as well as d-CAs, such as TweCAd (from the diatom Thalassiosira weissflogii)], f-CA, such as ZnTweCAf (from the same diatom, Thalassiosira weissflogii)], and g-CAs, such as PfaCA (from Plasmodium falciparum) [31,[40][41][42][43][44]. Among them, an interesting activation profile was observed for some of the cclass CAs, such as BpscCA.…”
Section: Activation Of C- D- F- and G-cas With Amino Acids And Aminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation studies were also performed recently against c-CAs, such as Zn-Cam and Co-Cam (from the Archaeon Methanosarcina thermpophila), BpscCA (from the pathogenic bacterium Burkhalderia pseudomallei), PhaCA (from the cyanobacterium Pseudoalteromonas haloplanktis), and CpsCA (from another cyanobacteriu, Colwellia psychrerythraea), as well as d-CAs, such as TweCAd (from the diatom Thalassiosira weissflogii)], f-CA, such as ZnTweCAf (from the same diatom, Thalassiosira weissflogii)], and g-CAs, such as PfaCA (from Plasmodium falciparum) [31,[40][41][42][43][44]. Among them, an interesting activation profile was observed for some of the cclass CAs, such as BpscCA.…”
Section: Activation Of C- D- F- and G-cas With Amino Acids And Aminesmentioning
confidence: 99%
“…Table 3. In vitro c-CA (Zn-Cam [31], Co-Cam [31], BpscCA [40], PhaCA [41], and CpsCA [41]), d-CA (TweCAd) [42], f-CA (ZnTweCAf) [43], and g-CA (PfaCA) [44] activation data with amines and amino acids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The inhibition of these enzymes with sulfonamide, anions and other derivatives was reported earlier 31–33 , but no activation studies of the two enzymes are available in the literature. Here we report the first activation study of BsuCA 1 and FtuCA with a panel of amino acids and amines, known to act as CAAs for enzymes belonging to various other genetic families 29–34 .…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme-activator complexes were thoroughly characterized for α-CAs of human origin, such as hCA I and II, by means of kinetic and X-ray crystallographic techniques, which allowed the identification of the activator-binding site within the CA cavity 8 , 9 , 21–29 . However, CAA research involving various activators has been relatively neglected compared with that of CAIs, with only a relatively limited number of studies focusing on activators of bacterial CAs 29 . Recently, it has been demonstrated that such activators may have pharmacological applications for enhancing cognition, in the management of CA deficiencies, for therapy memory and for obtaining artificial tissues a well as for investigating the effects of endogenous amino acids and amines on CA activity 30 .…”
Section: Introductionmentioning
confidence: 99%